Research-derived web design guidelines for older people - Kurniawan, Sri Hastuti; Zaphiris, Panayiotis (My University, 2005)
This paper presents the development of a set of research-derived ageing-centred Web design guidelines. An initial set of guidelines was first developed through an extensive review of the HCI and ageing literature and through employing a series of classification methods (card sorting and affinity diagrams) were employed as a means for obtaining a revised and more robust set of guidelines. A group of older Web users were then involved in evaluating the usefulness of the guidelines. To provide evaluation context for these users, two websites targeted to older people were used. This study makes several contributions to the field. First, it is perhaps the first manuscript that proposes ageing-friendly guidelines that are for most part backed by published studies. Second, the guidelines proposed in this study have been thoroughly examined through a series of expert and user verifications, which should give users of these guidelines confidence of their validity.
Keywords: Ageing; Web design guidelines; Elderly; Seniors; HCI